High-strength insulating Schiff base degradable epoxy resin material and preparation method thereof

By introducing the Schiff alkali chain segment of dynamic exchange reaction into the crosslinking network of epoxy resin materials, the synergistic problem of degradability and service performance of epoxy resin materials in a high insulation environment is solved, and efficient degradation and excellent insulation and mechanical properties are achieved.

CN119684573AActive Publication Date: 2025-03-25HEFEI UNIV OF TECH +1

Patent Information

Application Number
CN202510222260.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-03-25
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

It is difficult for existing epoxy resin materials to achieve synergies between degradability and service performance in high insulating service environments, and their glass transition temperature is not sufficient to meet the long-term operating performance requirements.

Method used

By constructing Schiff alkaline segments that can undergo dynamic exchange reactions between the molecular chains of the epoxy crosslinking network, and based on the structural design of Schiff alkaline segments between chains and optimization of the number of chains, the multi-dimensional performance coordinated regulation of highly degraded epoxy resin materials is achieved.

Benefits of technology

It realizes the high service performance requirements of epoxy resin materials in a high-insulating service environment, and at the same time improves the material's degradation ability and glass transition temperature, meeting the long-term operating performance requirements under multiple field coupling of electricity, force and heat.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684573A_ABST
    Figure CN119684573A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of epoxy resin, and particularly relates to a high-strength insulating Schiff base degradable epoxy resin material and a preparation method thereof. According to the invention, a step-by-step reaction is adopted, the molecular structure design of a Schiff base chain segment and the construction of a functional building block are firstly carried out, and then the Schiff base building block is introduced between cross-linked network molecular chains through the chain extension modification of resin molecules, so that the epoxy resin material is endowed with high-efficiency degradation capability in an acid solution, and a deep carrier trap is constructed in a cross-linked network; and the transport behavior of carriers in the network is regulated and controlled, so that the insulating property of the epoxy resin material is improved. Besides, through the synergistic effect of a rigid multi-benzene ring structure and a multi-flexible ether bond in an inter-chain Schiff base chain segment and the adjustability of the length of the Schiff base chain segment, the controllability of the packing tightness degree of molecular chains in an epoxy cross-linked network is also realized, and the mechanical strength of the epoxy resin material is enhanced; and the requirement of high service performance of the high-degradation epoxy resin material in a high-insulation service environment is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of degradable epoxy resin modification, and particularly relates to a high-strength insulating Schiff base degradable epoxy resin material and a preparation method thereof. Background Art

[0002] Epoxy resin is used as a core material for precision electronic device packaging, advanced electrical equipment manufacturing, and high-end power equipment insulation due to its excellent insulation, mechanical and chemical stability. However, after epoxy resin is cross-linked and cured, it forms a highly stable three-dimensional cross-linked network structure, making it difficult to degrade and recycle epoxy resin materials. my country's annual consumption of electrical epoxy can reach hundreds of thousands of tons. The environmental pollution and waste of resources caused by the retirement and disposal of thermosetting epoxy resin materials have become a major problem that needs to be solved urgently.

[0003] In response to the degradation and recycling problems of thermosetting epoxy resin materials, in 2011, French scholar Liberle proposed a revolutionary new technology for epoxy resin degradation. By introducing dynamic covalent bonds that can undergo dynamic exchange reactions into epoxy resin molecules. By applying specific external stimuli, the exchange reaction between the dynamic covalent bonds in the epoxy resin cross-linking network and the external medium is triggered, the directional breakage of the chemical bonds in the resin network is achieved, and the epoxy cross-linking network is efficiently deconstructed. However, although the introduction of dynamic covalent bonds in the epoxy resin cross-linking network gives the epoxy resin material high degradation characteristics, it also becomes an "unstable factor" in the network, which will lead to a decrease in the electrical, mechanical, thermal and other service performance of the epoxy resin material, especially when the epoxy resin material is operated for a long time in scenarios with high insulation requirements such as power equipment. The high insulation service environment is another key challenge for the long-term reliability of epoxy resin materials. Therefore, the synergy between the high degradability and high service performance of epoxy resin materials is a major problem that needs to be broken through.

[0004] In response to the above-mentioned problem of synergistic performance of epoxy resin materials, existing research has achieved a balance between the degradability and other service performance of epoxy resin materials by constructing a multi-level interlocking covalent adaptive cross-linking network. It mainly introduces multiple dynamic covalent bonds in the cross-linking network, and according to the stimulus response characteristics of different dynamic covalent bonds, while achieving the degradable functionalization of epoxy resin materials, it further takes into account the mechanical and thermal properties of epoxy resin materials. However, this epoxy resin material is not for high-insulation application scenarios, and there are no high requirements for the insulation performance of epoxy resin materials. Moreover, the glass transition temperature of this epoxy resin material is only 103°C at most, which cannot meet the long-term operation performance requirements of the material under the coupling of electrical, mechanical, and thermal fields. Therefore, for the high-insulation operation scenarios of epoxy resin materials, it is very important to propose an effective method that takes into account the degradation and service performance of epoxy insulation materials. Summary of the invention

[0005] In view of the above problems, one of the objects of the present invention is to provide a method for preparing a Schiff base-based degradable epoxy resin material with high strength insulation, by constructing Schiff base segments that can undergo dynamic exchange reactions between the molecular chains of the epoxy cross-linked network, and based on the structural design of the interchain Schiff base segments and the optimization of the number of segments, to achieve coordinated regulation of the multi-dimensional properties of the highly degradable epoxy resin material, and to achieve coordinated improvement of the mechanical and insulation properties of the degradable epoxy material constructed based on the interchain Schiff base segments.

[0006] To achieve the above object, the present invention adopts the following technical scheme: a method for preparing a high-strength insulating Schiff base degradable epoxy resin material, comprising the following steps: S1. Weigh a Schiff base building block, an epoxy resin and a phase transfer catalyst in a molar ratio of (0.1-0.3): 1: (0.001-0.003); the molecular structure of the Schiff base building block is: ; Among them, the R group is C 6 H 4 , C 12 H 8 O.C 13 H 10 , C 15 H 14 and C 13 H 8 F 6 One of; The epoxy resin and the Schiff base building block are mixed, stirred and dissolved at 90-120°C to form a uniform mixed solution, a phase transfer catalyst is added, the heating temperature is adjusted to 130-160°C, stirring is continued at this temperature for 6-12 hours, and cooling is performed after the reaction is completed to obtain the Schiff base chain extension modified epoxy resin; S2. Weigh the Schiff base chain-extending modified epoxy resin, the anhydride curing agent and the amine accelerator in a mass ratio of 100:(60-90):(0.005-0.015); The epoxy resin modified by Schiff base chain extension and the acid anhydride curing agent are placed in a reaction kettle, heated and stirred at 80-120°C to form a uniform mixed liquid, the mixed liquid is subjected to a first degassing treatment, an amine accelerator is added during the treatment, and the degassed mixed liquid is poured into a preheated mold, subjected to a second degassing treatment, cured, cooled to room temperature and then demolded, thereby obtaining an epoxy insulating material with interchain Schiff base segments.

[0007] Further improvement of the preparation method of Schiff base degradable epoxy resin material as high-strength insulation: Preferably, the epoxy resin described in step S1 is one or a combination of two or more of glycidyl ether, glycidyl ester, aliphatic and alicyclic epoxy resins.

[0008] Preferably, the phase transfer catalyst in step S1 is one or a combination of two or more of onium salts, open-chain polyethers, tertiary amines, crown ethers, thioethers and quaternary ammonium salts.

[0009] Preferably, the anhydride curing agent described in step S2 is one or a combination of two or more of phthalic anhydride, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride and methylnadic anhydride.

[0010] Preferably, the amine accelerator described in step S2 is one or a combination of two or more of aliphatic amines, alicyclic amines, aromatic amines, and heterocyclic amine accelerators.

[0011] Preferably, the specific process of the first degassing treatment, the second degassing treatment and curing in step S2 is as follows: the mixed liquid is degassed at a vacuum degree of 0.08~0.1MPa for 10~120min, an amine accelerator is added, and the vacuum degassing is continued for 5~20min, and the vacuum condition is removed, and the first degassing treatment is completed; then the mixed liquid is poured into a mold preheated to 80~120℃, placed under heating conditions of 120~140℃ for 5~30min, and the second degassing treatment is completed, and then pre-cured at 120~140℃ for 3~9h, and then placed at 150~170℃ for post-curing for 3~18h.

[0012] Preferably, the preparation method of the Schiff base building block in step S1 is as follows: S11, weighing kojic acid, a diamine compound and p-toluenesulfonic acid in a molar ratio of 2: (0.8-1.2): (0.02-0.1); S12. Dissolve kojic acid and diamine compounds in benzene according to the above-mentioned molar ratio, and stir them magnetically at 40-80°C until they are completely dissolved. Then add p-toluenesulfonic acid as a catalyst, adjust the heating temperature to 60-140°C, condense and reflux for 12-24 hours, and after the reaction is completed, filter and evaporate excess benzene to obtain a Schiff base building block product.

[0013] Preferably, the diamine compound described in step S11 and step S12 is one or a combination of two or more of 4,4'-diaminophenyl ether, p-phenylenediamine, 4,4'-methylenedianiline, 4,4'-(2,2-propylenediyl)diphenylamine and 4,4'-(perfluoropropane-2,2-diyl)diphenylamine.

[0014] Preferably, in step S1 and step S12, the progress of the chain extension modification reaction is tracked by thin layer chromatography.

[0015] The second object of the present invention is to provide a high-strength insulating Schiff base degradable epoxy resin material prepared by the preparation method of the high-strength insulating Schiff base degradable epoxy resin material described in any one of the above items.

[0016] Compared with the prior art, it has the following beneficial effects: 1) In order to overcome the problem that the existing technology is difficult to achieve the coordination of electrical, mechanical, thermal and other service performance of epoxy materials while realizing the degradable functionalization of epoxy materials, and cannot meet the performance requirements of long-term operation of epoxy materials in high insulation scenarios. The present invention provides a method for synergistically improving the insulation and mechanical properties of degradable epoxy resin materials based on the construction of interchain Schiff base segments. By constructing Schiff base segments that can undergo dynamic exchange reactions between the molecular chains of the epoxy cross-linked network, and based on the structural design of the interchain Schiff base segments and the optimization of the number of segments, the high service performance requirements of highly degradable epoxy resin materials in high insulation service environments are achieved. The main design ideas are as follows: The present invention adopts step-by-step reaction, first carries out the molecular structure design and functional building block construction of Schiff base segment, constructs the rigid multi-benzene ring Schiff base building block with pH response characteristics, and introduces the Schiff base segment into the molecular chain of cross-linked network by chain extension modification of resin molecule, so as to give epoxy resin material efficient degradation ability in acidic solution. Meanwhile, the introduction of interchain Schiff base segment can also construct deep carrier trap in cross-linked network, and then regulate the transport behavior of carrier in cross-linked network, suppress the proliferation of carrier inside material under high electric field, and realize the enhancement of insulation performance of epoxy cross-linked network. Meanwhile, by the construction of inter-molecular Schiff base segment, more flexible ether bonds and inter-chain rigid multi-benzene ring structure are introduced on the resin main chain, the synergistic effect of high rigid multi-benzene ring structure and multi-flexible ether bonds in inter-chain Schiff base segment, and the adjustability of Schiff base segment length, the controllable degree of molecular chain stacking tightness in epoxy cross-linked network is also realized, the rigidity and flexibility of epoxy cross-linked network are realized, so that the mechanical strength of epoxy insulating material can be synergistically enhanced. The steric hindrance effect of the rigid polybenzene ring structure can also inhibit the free rotation of the chain segments within the cross-linked network, increase the synergistic torsion barrier of the chain segments within the network, and thus improve the thermal properties of the epoxy cross-linked network to a certain extent.

[0017] 2) The Schiff base segments constructed between the molecular chains of the epoxy cross-linked network prepared by the present invention have pH response characteristics, and the -C=N dynamic covalent bonds in the segments can achieve chemical bond cleavage in acidic solutions, thereby achieving the purpose of depolymerizing the epoxy cross-linked network. At the same time, the response of the -C=N dynamic covalent bonds to temperature also gives the epoxy cross-linked network dynamics, thereby achieving the thermal remodeling and damage self-repair characteristics of epoxy insulation materials.

[0018] The present invention constructs a Schiff base segment with high electron affinity and low vertical ionization energy between the molecular chains of the epoxy cross-linked network. The introduction of the Schiff base segment can construct a deep carrier trap in the epoxy cross-linked network, increase the density of the carrier trap, and then regulate the transport behavior of the carriers in the epoxy cross-linked network, inhibit the proliferation of carriers inside the epoxy material under high field, and improve the insulation performance of the epoxy cross-linked network. At the same time, the adjustability of the Schiff base segment length in the epoxy cross-linked network also gives the epoxy cross-linked network a higher molecular chain packing density, thereby reducing the free volume ratio in the cross-linked network, weakening the motion response ability of the dipole to the electric field, thereby being able to achieve the improvement of the dielectric properties of the epoxy insulating material.

[0019] The rigid multi-benzene ring conjugated structure and the flexible freely rotatable methylene and ether bonds introduced into the resin molecular chain of the present invention can give the epoxy insulating material a more excellent mechanical strength. Specifically, the chain extension modification of the epoxy resin introduces more ether bonds into the main chain of the molecule, which can improve the ductility of the epoxy cross-linked network. At the same time, the introduction of rigid benzene rings between the resin molecular chains and cyclohexenyl groups on the molecular chain also increases the rigidity of the cross-linked network as a whole. The epoxy cross-linked network with synergistic rigidity and flexibility also gives the epoxy insulating material higher mechanical strength and ductility.

[0020] The Schiff base segments between molecular chains constructed in the epoxy cross-linked network of the present invention exhibit a certain conjugation. Therefore, the overall structure of the segments has a higher rigidity, which can inhibit the free rotation of flexible groups such as ether bonds on the resin molecular chain to a certain extent, thereby increasing the synergistic torsion barrier of the segments in the cross-linked network. At the same time, the construction of the Schiff base segments also introduces more -C=N cross-linking sites in the cross-linked network, and the -C=N double bonds have higher rigidity than the ester bonds formed by cross-linking of epoxy groups and acid anhydrides. This also makes the epoxy cross-linked network have a higher glass transition temperature after constructing the interchain Schiff base segments, and also makes the epoxy insulating material have a higher serviceable temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 is the NMR of the Schiff base building block in Example 1 1 H; Figure 2 is the NMR of the Schiff base building block in Example 1 13 C; Figure 3 is the NMR of the Schiff base building block in Example 4 1 H; Figure 4 is the NMR of the Schiff base building block in Example 4 13 C; Figure 5 is the NMR of the Schiff base building block in Example 4 19 F; Figure 6 It is the epoxy cross-linked network of Schiff base segments constructed between molecular chains in Example 2; Figure 7 It is the mass change curve of the epoxy insulation material samples prepared in Examples 1, 3, 5, 6, 7, 8 and Comparative Examples 1-3 during the degradation process. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific embodiments of the specification.

[0025] Example 1 This embodiment provides a method for preparing a high-strength insulating Schiff base degradable epoxy resin material, which specifically comprises the following steps: Step 1: Synthesis of Schiff base building blocks: Weigh 2 mol of kojic acid, 1 mol of 4,4'-diaminophenyl ether, and 0.04 mol of p-toluenesulfonic acid respectively. Dissolve kojic acid and 4,4'-diaminophenyl ether in benzene, and completely dissolve them by magnetic stirring under heating conditions at 60°C. Then add p-toluenesulfonic acid to the completely dissolved mixed solution. At this time, adjust the heating temperature to 120°C and condense and reflux for 12 hours, and use thin layer chromatography tracking method to track the reaction in real time. After the reaction is completed, filter and evaporate the excess benzene solvent to obtain Schiff base building block product 1.

[0026] Step 2: Schiff base chain extension modification reaction of epoxy resin: Weigh 0.1 mol of Schiff base building block, 1 mol of bisphenol A epoxy resin, and 0.001 mol of benzyl triethyl ammonium chloride respectively. Stir and dissolve the epoxy resin and Schiff base building block at 120°C to form a uniform mixed solution, add the phase transfer catalyst benzyl triethyl ammonium chloride to the mixed solution, and adjust the heating temperature to 160°C. Continue stirring at this heating temperature for 9 h. The chain extension modification reaction is tracked by thin layer chromatography, and the Schiff base chain extension modified bisphenol A epoxy resin can be obtained after the reaction is completed.

[0027] Step 3: Construction of epoxy cross-linked network containing Schiff base segments: Weigh 100g of Schiff base chain extension modified bisphenol A epoxy resin, 66g of phthalic anhydride curing agent, and 0.005g of DMP-30 accelerator respectively. Put the Schiff base chain segment extended modified bisphenol A epoxy resin and phthalic anhydride curing agent into the reactor and heat and stir at 100℃. After mixing into a uniform liquid phase, degassing is carried out under a vacuum degree of 0.1MPa. After degassing for 30min, DMP-30 accelerator is added to the mixed liquid, and vacuum degassing is continued for 5min. Remove the vacuum condition, pour the mixed liquid into the mold preheated to 100℃ in advance, and degas in an oven at 130℃ for 10min. Select pre-curing of 130℃ / 6h and post-curing of 160℃ / 6h. After the curing program is completed, the sample is naturally cooled to room temperature and demolded to obtain a high-strength insulating Schiff base degradable epoxy resin material.

[0028] Comparative Example 1 This comparative example provides a method for constructing a non-chain-extended modified bisphenol A epoxy cross-linked network, which specifically comprises the following steps: Weigh 100g of bisphenol A epoxy resin, 80g of phthalic anhydride curing agent, and 0.005g of DMP-30 accelerator respectively. Put bisphenol A epoxy resin and phthalic anhydride curing agent into a reactor and heat and stir at 100°C. After mixing into a uniform liquid phase, degassing is carried out under a vacuum degree of 0.1MPa. After degassing for 30 minutes, DMP-30 accelerator is added to the mixed liquid, and vacuum degassing is continued for 5 minutes. Remove the vacuum condition, pour the above mixed liquid into a mold preheated to 100°C in advance, and degas in an oven for 10 minutes. Select pre-curing of 130°C / 6h and post-curing of 160°C / 6h. After the curing program is completed, the sample is naturally cooled to room temperature and then demolded to obtain bisphenol A epoxy insulation material, and the performance test and characterization of the epoxy insulation material are carried out.

[0029] Example 2 This embodiment provides a method for preparing a high-strength insulating Schiff base degradable epoxy resin material, which specifically comprises the following steps: Step 1: Synthesis of Schiff base building blocks: Weigh 2 mol of kojic acid, 1 mol of p-phenylenediamine, and 0.04 mol of p-toluenesulfonic acid respectively. Dissolve kojic acid and p-phenylenediamine in benzene, and completely dissolve them in benzene by magnetic stirring under heating conditions of 60°C. Then add p-toluenesulfonic acid to the completely dissolved mixed solution. At this time, adjust the heating temperature to 120°C and condense and reflux. Continue magnetic stirring at this temperature for 12 h, and use thin layer chromatography tracking method to track the reaction in real time. After the reaction is completed, filter and evaporate the excess benzene solvent to obtain Schiff base building block product 2.

[0030] Step 2: Schiff base chain extension modification reaction of epoxy resin: Weigh 0.1 mol of Schiff base building block, 1 mol of bisphenol A epoxy resin, and 0.001 mol of benzyl triethyl ammonium chloride respectively. Stir and dissolve the epoxy resin and Schiff base building block at 120°C to form a uniform mixed solution. Add phase transfer catalyst benzyl triethyl ammonium chloride to the mixed solution, and further adjust the heating temperature to 160°C. Continue stirring at this heating temperature for 9 h. After the reaction is completed, the Schiff base chain-extended modified bisphenol A epoxy resin can be obtained.

[0031] Step 3: Construction of epoxy cross-linked network containing Schiff base segments: Weigh 100g of bisphenol A epoxy resin modified by Schiff base segment chain extension, 66g of phthalic anhydride curing agent, and 0.005g of DMP-30 accelerator respectively. Put the bisphenol A epoxy resin modified by Schiff base segment chain extension and phthalic anhydride curing agent into a reactor and heat and stir at 100℃. After mixing into a uniform liquid phase, degassing is carried out under a vacuum degree of 0.1MPa. After degassing for 30min, DMP-30 accelerator is added to the mixed liquid, and vacuum degassing is continued for 5min. Remove the vacuum condition, pour the mixed liquid into a mold preheated to 100℃ in advance, and degas in an oven at 130℃ for 10min. Use pre-curing of 130℃ / 6h and post-curing of 160℃ / 6h. After the program curing is completed, the sample is demoulded after naturally cooling to room temperature, and a high-strength insulating Schiff base degradable epoxy resin material is obtained.

[0032] Example 3 This embodiment provides a method for preparing a high-strength insulating Schiff base degradable epoxy resin material, which specifically comprises the following steps: Step 1: Synthesis of Schiff base building blocks: Weigh 2 mol of kojic acid, 1 mol of 4,4'-methylenedianiline, and 0.04 mol of p-toluenesulfonic acid respectively. Dissolve kojic acid and 4,4'-methylenedianiline in benzene, and completely dissolve them in benzene by magnetic stirring under heating conditions at 60°C. Then add p-toluenesulfonic acid to the completely dissolved mixed solution. At this time, adjust the heating temperature to 120°C and condense and reflux. Continue magnetic stirring at this temperature for 12 h, and use thin layer chromatography tracking to track the reaction in real time. After the reaction is completed, filter and evaporate the excess benzene solvent to obtain Schiff base building block product 3.

[0033] Step 2: Schiff base chain extension modification reaction of epoxy resin: Weigh 0.1 mol of Schiff base building block, 1 mol of bisphenol A epoxy resin, and 0.001 mol of benzyl triethyl ammonium chloride respectively. Stir and dissolve the epoxy resin and Schiff base building block at 120°C to form a uniform mixed solution. Add phase transfer catalyst benzyl triethyl ammonium chloride to the mixed solution, and further adjust the heating temperature to 160°C. Continue stirring at this heating temperature for 9 hours. After the reaction is completed, the Schiff base chain-extended modified bisphenol A epoxy resin can be obtained.

[0034] Step 3: Construction of epoxy cross-linked network containing Schiff base segments: Weigh 100g of bisphenol A epoxy resin modified by Schiff base segment chain extension, 66g of phthalic anhydride curing agent, and 0.005g of DMP-30 accelerator respectively. Put the bisphenol A epoxy resin modified by Schiff base segment chain extension and phthalic anhydride curing agent into a reactor and heat and stir at 100℃. After mixing into a uniform liquid phase, degassing is carried out under a vacuum degree of 0.1MPa. After degassing for 30min, DMP-30 accelerator is added to the mixed liquid, and vacuum degassing is continued for 5min. Remove the vacuum condition, pour the mixed liquid into a mold preheated to 100℃ in advance, and degas in an oven at 130℃ for 10min. Use pre-curing of 130℃ / 6h and post-curing of 160℃ / 6h. After the program curing is completed, the sample is demoulded after naturally cooling to room temperature, and a high-strength insulating Schiff base degradable epoxy resin material is obtained.

[0035] Example 4 This embodiment provides a method for preparing a high-strength insulating Schiff base degradable epoxy resin material, which specifically comprises the following steps: Step 1: Synthesis of Schiff base building blocks: Weigh 2 mol of kojic acid, 1 mol of 4,4'-(perfluoropropane-2,2-diyl)diphenylamine, and 0.04 mol of p-toluenesulfonic acid respectively. Dissolve kojic acid and 4,4'-(perfluoropropane-2,2-diyl)diphenylamine in benzene, and completely dissolve them in benzene by magnetic stirring under heating conditions at 60°C. Then add p-toluenesulfonic acid to the completely dissolved mixed solution. At this time, adjust the heating temperature to 120°C and condense and reflux. Continue magnetic stirring at this temperature for 12 h, and use thin layer chromatography tracking to track the reaction in real time. After the reaction is completed, filter and evaporate the excess benzene solvent to obtain Schiff base building block product 4.

[0036] Step 2: Schiff base chain extension modification reaction of epoxy resin: Weigh 0.1 mol of Schiff base building block, 1 mol of bisphenol A epoxy resin, and 0.001 mol of benzyl triethyl ammonium chloride respectively. Stir and dissolve the epoxy resin and Schiff base building block at 120°C to form a uniform mixed solution. Add phase transfer catalyst benzyl triethyl ammonium chloride to the mixed solution, and further adjust the heating temperature to 160°C. Continue stirring at this heating temperature for 9 hours. After the reaction is completed, the Schiff base chain-extended modified bisphenol A epoxy resin can be obtained.

[0037] Step 3: Construction of epoxy cross-linked network containing Schiff base segments: Weigh 100g of epoxy resin modified by Schiff base chain segment extension, 66g of phthalic anhydride curing agent, and 0.005g of DMP-30 accelerator respectively. Put the bisphenol A epoxy resin modified by Schiff base chain segment extension and phthalic anhydride curing agent into a reactor and heat and stir at 100℃. After mixing into a uniform liquid phase, degassing is carried out under a vacuum degree of 0.1MPa. After degassing for 30min, DMP-30 accelerator is added to the mixed liquid, and vacuum degassing is continued for 5min. Remove the vacuum condition, pour the mixed liquid into a mold preheated to 100℃ in advance, and degas in an oven at 130℃ for 10min. Use pre-curing of 130℃ / 6h and post-curing of 160℃ / 6h. After the program curing is completed, the sample is demoulded after naturally cooling to room temperature, and a high-strength insulating Schiff base degradable epoxy resin material is obtained.

[0038] A comparison is made between Examples 1, 2, 3 and 4 to explore the effect of the conjugated structure of the Schiff base segments between molecular chains on the performance of epoxy materials.

[0039] Example 5 This embodiment provides a method for preparing a high-strength insulating Schiff base degradable epoxy resin material, which specifically comprises the following steps: Step 1: Synthesis of Schiff base building blocks: Weigh 2 mol of kojic acid, 1 mol of 4,4'-diaminophenyl ether, and 0.04 mol of p-toluenesulfonic acid respectively. Dissolve kojic acid and 4,4'-diaminophenyl ether in benzene, and completely dissolve them in benzene by magnetic stirring under heating conditions at 60°C. Then add p-toluenesulfonic acid to the completely dissolved mixed solution. At this time, adjust the heating temperature to 120°C and condense and reflux. Continue magnetic stirring at this temperature for 12 hours, and use thin layer chromatography tracking method to track the reaction in real time. After the reaction is completed, filter and evaporate the excess benzene solvent to obtain Schiff base building block product 5.

[0040] Step 2: Schiff base chain extension modification reaction of epoxy resin: Weigh 0.2 mol of Schiff base building block, 1 mol of bisphenol A epoxy resin, and 0.002 mol of benzyl triethyl ammonium chloride respectively. Stir and dissolve the epoxy resin and Schiff base building block at 120°C to form a uniform mixed solution. Add phase transfer catalyst benzyl triethyl ammonium chloride to the mixed solution, and further adjust the heating temperature to 160°C. Continue stirring at this heating temperature for 9 h. After the reaction is completed, the Schiff base chain-extended modified bisphenol A epoxy resin can be obtained.

[0041] Step 3: Construction of epoxy cross-linked network containing Schiff base segments: Weigh 100g of epoxy resin modified by Schiff base segment chain extension, 53g of phthalic anhydride curing agent, and 0.005g of DMP-30 accelerator respectively. Put the bisphenol A epoxy resin modified by Schiff base segment chain extension and phthalic anhydride curing agent into the reactor and heat and stir at 100℃. After mixing into a uniform liquid phase, degassing is carried out under a vacuum degree of 0.1MPa. After degassing for 30min, DMP-30 accelerator is added to the mixed liquid, and vacuum degassing is continued for 5min. Remove the vacuum condition, pour the mixed liquid into the mold preheated to 100℃ in advance, and degas in an oven at 130℃ for 10min. Select pre-curing of 130℃ / 6h and post-curing of 160℃ / 6h. After the program curing is completed, the sample is naturally cooled to room temperature and demolded to obtain a high-strength insulating Schiff base degradable epoxy resin material.

[0042] Example 6 This embodiment provides a method for preparing a high-strength insulating Schiff base degradable epoxy resin material, which specifically comprises the following steps: Step 1: Synthesis of Schiff base building blocks: Weigh 2 mol of kojic acid, 1 mol of 4,4'-diaminophenyl ether, and 0.04 mol of p-toluenesulfonic acid respectively. Dissolve kojic acid and 4,4'-diaminophenyl ether in benzene, and completely dissolve them in benzene by magnetic stirring under heating conditions at 60°C. Then add p-toluenesulfonic acid to the completely dissolved mixed solution. At this time, adjust the heating temperature to 120°C and condense and reflux. Continue magnetic stirring at this temperature for 12 hours, and use thin layer chromatography tracking method to track the reaction in real time. After the reaction is completed, filter and evaporate the excess benzene solvent to obtain Schiff base building block product 6.

[0043] Step 2: Schiff base chain extension modification reaction of epoxy resin: Weigh 0.3 mol of Schiff base building block, 1 mol of bisphenol A epoxy resin, and 0.003 mol of benzyl triethyl ammonium chloride respectively. Stir and dissolve the weighed epoxy resin and Schiff base building block at 120°C to form a uniform mixed solution. Add phase transfer catalyst benzyl triethyl ammonium chloride to the mixed solution, and further adjust the heating temperature to 160°C. Continue stirring at this heating temperature for 9 h. After the reaction is completed, the Schiff base chain-extended modified bisphenol A epoxy resin can be obtained.

[0044] Step 3: Construction of epoxy cross-linked network containing Schiff base segments: Weigh 100g of epoxy resin modified by Schiff base segment chain extension, 39g of phthalic anhydride curing agent, and 0.005g of DMP-30 accelerator respectively. Put the bisphenol A epoxy resin modified by Schiff base segment chain extension and phthalic anhydride curing agent into the reactor and heat and stir at 100℃. After mixing into a uniform liquid phase, degassing is carried out under a vacuum degree of 0.1MPa. After degassing for 30min, DMP-30 accelerator is added to the mixed liquid, and vacuum degassing is continued for 5min. Remove the vacuum condition, pour the mixed liquid into the mold preheated to 100℃ in advance, and degas in an oven at 130℃ for 10min. Select pre-curing of 130℃ / 6h and post-curing of 160℃ / 6h. After the curing program is completed, the sample is demolded after naturally cooling to room temperature, and a high-strength insulating Schiff base degradable epoxy resin material is obtained.

[0045] Examples 1, 5, and 6 are compared to explore the effect of the content of Schiff base segments between molecular chains on the performance of epoxy materials. In Examples 1, 5, and 6, due to the change in the content of Schiff base blocks after the resin chain extension modification, the epoxy value of the epoxy resin after chain extension modification will change, which triggers a corresponding change in the content of the epoxy resin curing agent component. The content of phthalic anhydride curing agent in Examples 1, 5, and 6 is 66 g, 53 g, and 39 g, respectively.

[0046] Example 7 This embodiment provides a method for preparing a high-strength insulating Schiff base degradable epoxy resin material, which specifically comprises the following steps: Step 1: Synthesis of Schiff base building blocks: Weigh 2 mol of kojic acid, 1 mol of 4,4'-diaminophenyl ether, and 0.04 mol of p-toluenesulfonic acid respectively. Dissolve the weighed kojic acid and 4,4'-diaminophenyl ether in benzene, and completely dissolve them in benzene by magnetic stirring under heating conditions at 60°C. Then add p-toluenesulfonic acid to the completely dissolved mixed solution. At this time, adjust the heating temperature to 120°C and condense and reflux. Continue magnetic stirring at this temperature for 12 hours, and use thin layer chromatography tracking method to track the reaction in real time. After the reaction is completed, filter and evaporate the excess benzene solvent to obtain Schiff base building block product 7.

[0047] Step 2: Schiff base chain extension modification reaction of epoxy resin: Weigh 0.1 mol of Schiff base building block, 1 mol of bisphenol F epoxy resin, and 0.001 mol of benzyl triethyl ammonium chloride respectively. Stir and dissolve the epoxy resin and Schiff base building block at 120°C to form a uniform mixed solution. Add phase transfer catalyst benzyl triethyl ammonium chloride to the mixed solution, and further adjust the heating temperature to 160°C. Continue stirring at this heating temperature for 9 h. After the reaction is completed, the Schiff base chain-extended modified bisphenol F epoxy resin can be obtained.

[0048] Step 3: Construction of epoxy cross-linked network containing Schiff base segments: Weigh 100g of bisphenol F epoxy resin modified by Schiff base segment chain extension, 76g of phthalic anhydride curing agent, and 0.005g of DMP-30 accelerator respectively. Put the bisphenol F epoxy resin modified by Schiff base segment chain extension and phthalic anhydride curing agent into a reactor and heat and stir at 100℃. After mixing into a uniform liquid phase, degassing is carried out under a vacuum degree of 0.1MPa. After degassing for 30min, DMP-30 accelerator is added to the mixed liquid, and vacuum degassing is continued for 5min. Remove the vacuum condition, pour the mixed liquid into a mold preheated to 100℃ in advance, and degas in an oven at 130℃ for 10min. Select pre-curing of 130℃ / 6h and post-curing of 160℃ / 6h. After the program curing is completed, the sample is naturally cooled to room temperature and demolded to obtain a high-strength insulating Schiff base degradable epoxy resin material.

[0049] Comparative Example 2 This comparative example provides a method for constructing a non-chain-extended modified bisphenol F epoxy cross-linked network, which specifically comprises the following steps: Weigh 100g of bisphenol F epoxy resin, 80g of phthalic anhydride curing agent, and 0.005g of DMP-30 accelerator respectively. Put bisphenol A epoxy resin and phthalic anhydride curing agent into a reactor and heat and stir at 100°C. After mixing into a uniform liquid phase, degassing is carried out under a vacuum degree of 0.1MPa. After degassing for 30 minutes, DMP-30 accelerator is added to the mixed liquid, and vacuum degassing is continued for 5 minutes. Remove the vacuum condition, pour the mixed liquid into a mold preheated to 100°C in advance, and degas in an oven for 10 minutes. Select pre-curing of 130°C / 6h and post-curing of 160°C / 6h. After the curing program is completed, the sample is naturally cooled to room temperature and demolded to obtain bisphenol F epoxy insulation material, and the performance test and characterization of the epoxy insulation material are carried out.

[0050] Example 8 This embodiment provides a method for preparing a high-strength insulating Schiff base degradable epoxy resin material, which specifically comprises the following steps: Step 1: Synthesis of Schiff base building blocks: Weigh 2 mol of kojic acid, 1 mol of 4,4'-diaminophenyl ether, and 0.04 mol of p-toluenesulfonic acid respectively. Dissolve kojic acid and 4,4'-diaminophenyl ether in benzene, and completely dissolve them in benzene by magnetic stirring under heating conditions at 60°C. Then add p-toluenesulfonic acid to the completely dissolved mixed solution. At this time, adjust the heating temperature to 120°C and condense and reflux. Continue magnetic stirring at this temperature for 12 hours, and use thin layer chromatography tracking method to track the reaction in real time. After the reaction is completed, filter and evaporate the excess benzene solvent to obtain Schiff base building block product 8.

[0051] Step 2: Schiff base chain extension modification reaction of epoxy resin: Weigh 0.1 mol of Schiff base building block, 1 mol of bisphenol AF epoxy resin, and 0.001 mol of benzyltriethylammonium chloride respectively. Stir and dissolve the epoxy resin and Schiff base building block at 120°C to form a uniform mixed solution. Add phase transfer catalyst benzyltriethylammonium chloride to the mixed solution, and further adjust the heating temperature to 160°C. Continue stirring at this heating temperature for 9 h. After the reaction is completed, the Schiff base chain-extended modified bisphenol AF epoxy resin can be obtained.

[0052] Step 3: Construction of epoxy cross-linked network containing Schiff base segments: Weigh 100g of bisphenol AF epoxy resin modified by Schiff base segment chain extension, 68g of phthalic anhydride curing agent, and 0.005g of DMP-30 accelerator respectively. Put the bisphenol AF epoxy resin modified by Schiff base segment chain extension and phthalic anhydride curing agent into a reactor and heat and stir at 100℃. After mixing into a uniform liquid phase, degassing is carried out under a vacuum degree of 0.1MPa. After degassing for 30min, DMP-30 accelerator is added to the mixed liquid, and vacuum degassing is continued for 5min. The vacuum condition is removed and the degassing treatment is completed; the mixed liquid is poured into a mold preheated to 100℃ in advance, and degassed in an oven at 130℃ for 10min. Pre-curing at 130℃ / 6h and post-curing at 160℃ / 6h are selected. After the program curing is completed, the sample is naturally cooled to room temperature and demolded to obtain a high-strength insulating Schiff base degradable epoxy resin material.

[0053] Comparative Example 3 This comparative example provides a method for constructing an epoxy cross-linked network of unextended modified bisphenol AF, which specifically comprises the following steps: Weigh 100g of bisphenol AF epoxy resin, 80g of phthalic anhydride curing agent, and 0.005g of DMP-30 accelerator respectively. Put the bisphenol AF epoxy resin and phthalic anhydride curing agent into a reactor and heat and stir at 100°C. After mixing into a uniform liquid phase, degassing is carried out under a vacuum degree of 0.1MPa. After degassing for 30 minutes, DMP-30 accelerator is added to the mixed liquid, and vacuum degassing is continued for 5 minutes. Remove the vacuum condition, pour the above mixed liquid into a mold preheated to 100°C in advance, and degas in an oven for 10 minutes. Select pre-curing of 130°C / 6h and post-curing of 160°C / 6h. After the curing program is completed, the sample is naturally cooled to room temperature and demolded to obtain bisphenol AF epoxy insulation material, and the performance test and characterization of the epoxy insulation material are carried out.

[0054] Comparisons between Comparative Examples 1, 2, and 3 and Examples 1, 7, and 8 were made to explore the performance improvement effect of the Schiff base segment on chain extension modification of different epoxy resins.

[0055] Example 9 This embodiment provides a method for preparing a high-strength insulating Schiff base degradable epoxy resin material, which specifically comprises the following steps: Step 1: Synthesis of Schiff base building blocks: Weigh 2 mol of kojic acid, 1 mol of 4,4'-(2,2-propylenediyl)diphenylamine, and 0.04 mol of p-toluenesulfonic acid respectively. Dissolve kojic acid and 4,4'-(2,2-propylenediyl)diphenylamine in benzene, and completely dissolve them by magnetic stirring under heating conditions at 60°C. Then add p-toluenesulfonic acid to the completely dissolved mixed solution. At this time, adjust the heating temperature to 120°C and condense and reflux for 12 h, and use thin layer chromatography tracking method to track the reaction in real time. After the reaction is completed, filter and evaporate the excess benzene solvent to obtain Schiff base building block product 9.

[0056] Step 2: Schiff base chain extension modification reaction of epoxy resin: Weigh 0.1 mol of Schiff base building block, 1 mol of bisphenol A epoxy resin, and 0.001 mol of benzyl triethyl ammonium chloride respectively. Stir and dissolve the epoxy resin and Schiff base building block at 120°C to form a uniform mixed solution, add the phase transfer catalyst benzyl triethyl ammonium chloride to the mixed solution, and adjust the heating temperature to 160°C. Continue stirring at this heating temperature for 9 h. The chain extension modification reaction is tracked by thin layer chromatography, and the Schiff base chain extension modified bisphenol A epoxy resin can be obtained after the reaction is completed.

[0057] Step 3: Construction of epoxy cross-linked network containing Schiff base segments: Weigh 100g of Schiff base chain extension modified bisphenol A epoxy resin, 60g of phthalic anhydride curing agent, and 0.005g of DMP-30 accelerator respectively. Put the Schiff base chain segment extended modified bisphenol A epoxy resin and phthalic anhydride curing agent into the reactor and heat and stir at 100℃. After mixing into a uniform liquid phase, degassing is carried out under a vacuum degree of 0.1MPa. After degassing for 120min, DMP-30 accelerator is added to the mixed liquid, and vacuum degassing is continued for 10min. Remove the vacuum condition, pour the mixed liquid into the mold preheated to 80℃ in advance, and degas in an oven at 130℃ for 10min. Select pre-curing of 120℃ / 9h and post-curing of 170℃ / 3h. After the program curing is completed, the sample is naturally cooled to room temperature and demolded to obtain a high-strength insulating Schiff base degradable epoxy resin material.

[0058] Example 10 This embodiment provides a method for preparing a high-strength insulating Schiff base degradable epoxy resin material, which specifically comprises the following steps: Step 1: Synthesis of Schiff base building blocks: Weigh 2 mol of kojic acid, 0.8 mol of 4,4'-(2,2-propylenediyl)diphenylamine, and 0.02 mol of p-toluenesulfonic acid respectively. Dissolve kojic acid and 4,4'-(2,2-propylenediyl)diphenylamine in benzene, and completely dissolve them by magnetic stirring under heating conditions at 40°C. Then add p-toluenesulfonic acid to the completely dissolved mixed solution. At this time, adjust the heating temperature to 80°C and condense and reflux for 12 hours, and use thin layer chromatography tracking method to track the reaction in real time. After the reaction is completed, filter and evaporate the excess benzene solvent to obtain Schiff base building block product 10.

[0059] Step 2: Schiff base chain extension modification reaction of epoxy resin: Weigh 0.1mol of Schiff base building block, 1mol of bisphenol A epoxy resin, and 0.001mol of benzyl triethyl ammonium chloride respectively. Stir and dissolve the epoxy resin and Schiff base building block at 90°C to form a uniform mixed solution, add the phase transfer catalyst benzyl triethyl ammonium chloride to the mixed solution, and adjust the heating temperature to 130°C. Continue stirring at this heating temperature for 12 hours. The chain extension modification reaction is tracked by thin layer chromatography. When the reaction is completed, the Schiff base chain extension modified bisphenol A epoxy resin can be obtained.

[0060] Step 3: Construction of epoxy cross-linked network containing Schiff base segments: Weigh 100g of Schiff base chain extension modified bisphenol A epoxy resin, 90g of phthalic anhydride curing agent, and 0.015g of DMP-30 accelerator respectively. Put the Schiff base chain segment extended modified bisphenol A epoxy resin and phthalic anhydride curing agent into the reactor and heat and stir at 120℃. After mixing into a uniform liquid phase, degassing is carried out under a vacuum degree of 0.1MPa. After degassing for 10min, DMP-30 accelerator is added to the mixed liquid, and vacuum degassing is continued for 20min. Remove the vacuum condition, pour the mixed liquid into the mold preheated to 100℃ in advance, and degas in an oven at 140℃ for 5min. Select pre-curing at 140℃ / 3h and post-curing at 150℃ / 18h. After the program curing is completed, the sample is naturally cooled to room temperature and demolded to obtain a high-strength insulating Schiff base degradable epoxy resin material.

[0061] Embodiment 11 Step 1: Synthesis of Schiff base building blocks: Weigh 2 mol of kojic acid, 1.2 mol of 4,4'-(2,2-propylenediyl)diphenylamine, and 0.1 mol of p-toluenesulfonic acid respectively. Dissolve kojic acid and 4,4'-(2,2-propylenediyl)diphenylamine in benzene, and completely dissolve them by magnetic stirring under heating conditions at 80°C. Then add p-toluenesulfonic acid to the completely dissolved mixed solution. At this time, adjust the heating temperature to 140°C and condense and reflux for 24 hours, and use thin layer chromatography tracking method to track the reaction in real time. After the reaction is completed, filter and evaporate the excess benzene solvent to obtain Schiff base building block product 11.

[0062] Step 2: Schiff base chain extension modification reaction of epoxy resin: Weigh 0.3 mol of Schiff base building block, 1 mol of bisphenol A epoxy resin, and 0.003 mol of benzyl triethyl ammonium chloride respectively. Stir and dissolve the epoxy resin and Schiff base building block at 120°C to form a uniform mixed solution. Add the phase transfer catalyst benzyl triethyl ammonium chloride to the mixed solution, adjust the heating temperature to 160°C, and continue stirring at this heating temperature for 6 h. The chain extension modification reaction is tracked by thin layer chromatography. When the reaction is completed, the Schiff base chain extension modified bisphenol A epoxy resin can be obtained.

[0063] Step 3: Construction of epoxy cross-linked network containing Schiff base segments: Weigh 100g of Schiff base chain extension modified bisphenol A epoxy resin, 80g of phthalic anhydride curing agent, and 0.01g of DMP-30 accelerator respectively. Put the Schiff base chain segment extended modified bisphenol A epoxy resin and phthalic anhydride curing agent into the reactor and heat and stir at 80℃. After mixing into a uniform liquid phase, degassing is carried out under a vacuum degree of 0.08MPa. After degassing for 30min, DMP-30 accelerator is added to the mixed liquid, and vacuum degassing is continued for 5min. Remove the vacuum condition, pour the mixed liquid into the mold preheated to 120℃ in advance, and degas in an oven at 120℃ for 30min. Select pre-curing 130℃ / 6h and post-curing 160℃ / 6h. After the program curing is completed, the sample is naturally cooled to room temperature and demolded to obtain a high-strength insulating Schiff base degradable epoxy resin material.

[0064] A comparison is made between Examples 9, 10 and 11 to explore the effects of the synthetic material ratio and process parameters of the Schiff base building block on the performance improvement of the epoxy resin chain extension modification.

[0065] The method of testing the embodiments or comparative examples of the present application is as follows: Epoxy value test of epoxy resin: The epoxy value of epoxy resin before and after Schiff base chain extension modification was determined according to the test requirements of GB-T1677-2008: ;

[0066] Where, V is the volume of standard sodium hydroxide solution consumed by the sample, ml; V 0 ——The volume of standard sodium hydroxide solution consumed by the blank sample, ml; C——The equivalent concentration of the sodium hydroxide standard solution, mol / L; W——The mass of the sample, g.

[0067] AC breakdown strength test: According to the test standard of GB / T 1408.1-2016 "Electrical Strength Test Method for Insulating Materials", the breakdown strength of the samples under the action of short-term electric field was measured at a voltage increase rate of 2 kV / s. The measurement environment temperature was 25 ℃, the test sample was a disc with a diameter of 100 mm and a thickness of 1 mm, the test voltage frequency was 50 Hz, 3 finished products were taken for each sample, 3 points were tested for each sample, and 9 breakdown data were obtained for each sample. The test results were averaged and the Weibull distribution was used to calculate the breakdown strength.

[0068] Tensile strength test: According to the test standard of GB / T2567-2021 "Test method for properties of cast resin bodies", a universal mechanical testing machine is used to measure the elastic modulus, tensile strength, tensile elongation and fracture toughness of the sample. The test sample is cast according to the technical conditions specified in GB / T2567-2008. The test temperature is 25°C and the relative humidity is 50%. When measuring the tensile strength, the test speed is 10mm / min, the arbitration test speed is 2mm / min, and when measuring other properties, the test speed is 2mm / min. Each sample is tested 3 times and the measurement results are averaged.

[0069] Glass transition temperature test: According to the national standard GB / T 40396-2021 "Test method for glass transition temperature of polymer-based composite materials - Dynamic mechanical analysis (DMA)", the glass transition temperature of the material is tested by a dynamic thermomechanical analyzer. The test mode is single and double cantilever mode. The test conditions are air atmosphere, the heating rate is 5℃ / min, the loading frequency is 1Hz, the temperature is increased from room temperature to 250℃, and then the temperature is increased to 250℃ again at the same rate after cooling to room temperature. The program heating is terminated after the modulus change tends to be flat, and the glass transition temperature of the test material sample is obtained by processing the test curve.

[0070] Chemical degradation performance test: select epoxy material samples of the same mass and size, place them in a degradation reactor, and chemically degrade them in a degradation solution at 100°C. The degradation rate of the material is calculated based on the degradation time required for the complete degradation of the epoxy material samples. Five groups of sample strips are taken from each group of samples, and the degradation rate is the average value of the five groups of sample strips.

[0071] Figure 1 is the NMR of the Schiff base building block in Example 1 1H; Figure 2 is the NMR of the Schiff base building block in Example 1 13 C; Figure 3 is the NMR of the Schiff base building block in Example 4 1 H; Figure 4 is the NMR of the Schiff base building block in Example 4 13 C; Figure 5 is the NMR of the Schiff base building block in Example 4 19 F. The performance characterization results of the epoxy insulation materials obtained in Examples 1 to 11 and Comparative Examples 1 to 3 are shown in Tables 1 to 2.

[0072] Among them, Example 1 is an epoxy insulating material obtained by cross-linking and curing a bisphenol A epoxy resin modified by chain extension using 4,4-diaminophenyl ether as a diamine compound to construct a Schiff base segment, and cross-linking and curing a bisphenol A epoxy resin modified by chain extension as a resin matrix. Comparative Example 1 is an epoxy insulating material obtained by cross-linking and curing a bisphenol A epoxy resin without Schiff base segment chain extension modification. Examples 1, 2, 3, 4 and 9 respectively select different diamine compounds, and use them to construct Schiff base segments with different conjugated structures, and then use them to extend and modify the bisphenol A epoxy resin, introduce Schiff base segments with different polyphenyl ring conjugated structures between the molecular chains of the epoxy cross-linked network, and realize the regulation of the service performance of the epoxy cross-linked network. Examples 1, 5 and 6 change the content of the Schiff base segment constructed between the molecular chains in the cross-linked network to compare and explore the influence of the Schiff base segment content between the molecular chains on the service performance of the epoxy cross-linked network. Examples 1, 7 and 8 respectively selected bisphenol A, bisphenol F and bisphenol AF epoxy resins as the resin matrix to explore the compatibility of Schiff base segments with the epoxy resin system and the construction of molecular chain segments on the performance improvement effect of epoxy insulation materials after cross-linking and curing. Examples 9, 10 and 11 adjusted the synthetic raw material ratio and process parameters of the Schiff base building block, and compared the three examples to explore the effect of the synthetic material ratio and process parameters of the Schiff base building block on the performance improvement effect of the epoxy resin chain extension modification.

[0073] Table 1 Comparison of performance parameters of epoxy resin after Schiff base chain extension modification in the examples ; As shown in Table 1, by measuring the epoxy value of the epoxy resin modified by Schiff base chain extension, it can be found that compared with the modified comparative example 1, in Examples 1, 2, 3, 4 and 9, after the epoxy resin is subjected to molecular chain extension modification, the epoxy value of the epoxy resin will be reduced to a certain extent, because the growth of the resin molecular chain after chain extension and the reduction of the content of epoxy groups on the resin main chain. And in Examples 1, 5 and 6, by changing the content of the Schiff base chain extension modifier during the chain extension process of the epoxy resin, the epoxy value of the modified epoxy resin will gradually decrease. In Examples 1, 7 and 8, the modification of the Schiff base chain extension modifier has a good chain extension modification effect for different epoxy resins, which also illustrates the adaptability of the developed Schiff base chain extension modifier to the epoxy resin system. The measured epoxy value of the epoxy resin after chain extension is also basically consistent with the theoretical epoxy value.

[0074] In addition, combined Figures 1 to 5 The NMR of the Schiff base building blocks synthesized in Example 1 and Example 4 1 H. 13 C and 19 F spectrum analysis shows that the molecular structure of the synthesized Schiff base building block has a good correspondence with the H, C and F atoms under the corresponding chemical shift in the nuclear magnetic resonance spectrum. This also shows that the Schiff base building block synthesized in the above examples and the chain extension modification reaction of the epoxy resin are consistent with the expectations. Examples 1, 2, 3, 4 and 9 respectively select diamine compounds of different structures, and use them to construct Schiff base segments of different conjugated structures, corresponding to the molecular structure of the Schiff base building block, the R group is C 6 H 4 , C 12 H 8 O.C 13 H 10 , C 13 H 8 F 6 and C 15 H 14The situation verifies the influence of the Schiff base building block structure between the resin molecular chains on the service performance of the epoxy cross-linked network. In Examples 1, 5 and 6, the content of the Schiff base segment between the molecular chains in the cross-linked network was further changed to explore the influence of the content of the Schiff base segment between the chains on the service performance of the epoxy cross-linked network. In Examples 1, 7 and 8, bisphenol A, bisphenol F and bisphenol AF epoxy resins were selected as resin matrices, respectively, to explore the compatibility of the Schiff base segment with the epoxy resin system and the effect of the construction of the molecular chain segments on the performance improvement of the epoxy insulating material after cross-linking and curing, and the universality of this method for improving the performance of epoxy resins has been verified. In Examples 9, 10 and 11, by changing the ratio of the raw materials kojic acid, diamine compounds and p-toluenesulfonic acid in the Schiff base building block, and further adjusting the synthesis process parameters of the Schiff base building block, the influence of the above variables on the service performance of the epoxy cross-linked network was studied, and the optimal Schiff base building block raw material ratio and the optimal synthesis process parameters were obtained.

[0075] By measuring the viscosity value of the epoxy resin after Schiff base chain extension modification, it can also be found that compared with the epoxy resin without chain extension modification (Comparative Examples 1, 2, and 3), the viscosity value of the epoxy resin after Schiff base chain extension modification will increase to a certain extent. In addition, by comparing the viscosity values ​​of the epoxy resin after chain extension with different contents of Schiff base chain extenders in Examples 1, 5, and 6, it can be seen that as the content of the chain extender modifier increases, the viscosity of the epoxy resin will increase accordingly. The increase in the viscosity of the epoxy resin matrix after chain extension modification can inhibit the sedimentation of the inorganic reinforcing filler in the resin to a certain extent, because the gravity suspension force on the inorganic reinforcing filler in the vertical direction of the resin matrix can be balanced. This has important practical significance for the development of high-performance epoxy composite insulating materials for high-end power equipment.

[0076] Table 2 Performance comparison of epoxy insulation materials in the examples and comparative examples ; As shown in Table 2, through comparative analysis of the multi-dimensional properties of epoxy insulation materials in comparative examples and embodiments, it can be seen that constructing Schiff base segments between cross-linked network molecular chains can effectively improve the insulation, mechanical, thermal and chemical degradability of epoxy materials.

[0077] Figure 6It is the epoxy cross-linked network of the Schiff base segment constructed between the molecular chains in Example 2; in terms of the dielectric strength of the epoxy insulating material, the dielectric strength of the unmodified bisphenol A epoxy material in Comparative Example 1 is only 35.13kV / mm, but after the Schiff base segment is constructed between the molecular chains of the cross-linked network, the dielectric strength of the epoxy material has been significantly improved. The results of Comparative Example 1, Examples 1, 5, and 6 show that with the increase in the number of Schiff base segments constructed between the molecular chains, the dielectric strength of the epoxy material will show a trend of first rising and then falling. When the amount ratio of epoxy resin to Schiff base segment is 1:0.2, the dielectric strength of the epoxy material is the highest, which can reach 39.19kV / mm, which is 11.5% higher than that of the epoxy insulating material without Schiff base segment. This is also related to the effect of the introduction of deep carrier traps in the network on carrier transport behavior. The performance results of the epoxy materials of Comparative Example 1 and Examples 1, 2, 3, 4 and 9 show that by changing the molecular structure of the Schiff base segment, carrier traps of different depths can be constructed between the molecular chains of the cross-linked network, and the regulation of the carrier transport behavior in the epoxy cross-linked network can be achieved, thereby improving the dielectric strength of the epoxy insulating material. When 4,4'-(perfluoropropane-2,2-diyl) diphenylamine is selected as a diamine compound to construct a Schiff base building block and introduced into the epoxy cross-linked network, the dielectric strength of the epoxy insulating material can reach 42.38kV / mm, which is increased by nearly 20%. In addition, when the Schiff base building block is used to extend the chain of bisphenol F and bisphenol AF epoxy resins, the dielectric strength of the epoxy insulating material is increased by a certain degree compared to that of the unmodified one. This also shows that the technical method has good adaptability for enhancing the performance of the epoxy resin system, and also shows that the technical method is a universal method for improving the performance of epoxy resins. This technical method has great reference significance for the development of epoxy resin materials with high degradation and high insulation for high-end power equipment.

[0078] In terms of the tensile strength of epoxy insulating materials, the tensile strength of unmodified bisphenol A epoxy insulating materials in comparative example 1 is only 73.2MPa. After the Schiff base segments are constructed in the cross-linked network in Examples 1, 2, 3, 4 and 9, the tensile strength of epoxy insulating materials is significantly improved, and the tensile strength of epoxy materials can reach up to 86.7MPa, which is 18.4% higher than that of unmodified. This is also related to the joint action of the rigid Schiff base segments between the chains and the flexible ether bonds on the chains. When more Schiff base segments are introduced between the molecular chains, the tensile strength of epoxy insulating materials will also show a change pattern of first rising and then falling. When the amount ratio of epoxy resin to Schiff base modifier is 1:0.2, the tensile strength of epoxy insulating materials can reach up to 89.1MPa.

[0079] The significant increase in the tensile strength of epoxy insulation materials also further reduces the risk of cracking during the operation of the materials, and also provides a guarantee for the safe and stable long-term operation of power equipment. At the same time, Schiff base chain extension modification has a significant performance enhancement effect on bisphenol F and bisphenol AF epoxy resins. Among them, the tensile strength of bisphenol F epoxy insulation material increased from 76.1MPa to 82.7MPa, and the tensile strength of bisphenol AF epoxy insulation material increased from 70.2MPa to 81.3MPa, with the maximum increase of 15.8%.

[0080] In terms of the glass transition temperature of epoxy insulating materials, the glass transition temperature of the unmodified bisphenol A epoxy insulating material in Comparative Example 1 is only 136°C, while in Examples 1, 5 and 6, when 4,4-diaminophenyl ether is selected as a diamine compound to construct a rigid conjugated Schiff base segment between the molecular chains of the cross-linked network, the glass transition temperature of the epoxy insulating material is the highest when the resin and the Schiff base chain extender modifier are 1:0.3, which can reach 162°C. This also shows that the introduction of rigid Schiff base segments has enhanced the overall rigidity of the cross-linked network, and more interchain Schiff base segments have a stronger inhibitory effect on the free rotation of the groups in the network, increasing the synergistic torsion barrier, and significantly improving the glass transition temperature of the epoxy cross-linked network. In Examples 1, 2, 3, 4 and 9, the design and construction of Schiff base segments of different rigidity and chain length have a certain effect on improving the thermal properties of epoxy insulating materials. When different Schiff base segments are introduced into the network, the glass transition temperature of the epoxy insulation material is in the range of 145~152℃. The Schiff base segment constructed by using 4,4'-(perfluoropropane-2,2-diyl) diphenylamine has a better effect on improving the glass transition temperature of the epoxy insulation material, which may also be related to the CF 3 The higher chemical bond energy of the group is related to stability. In addition, the interchain Schiff base segments constructed in the cross-linked network have a significant enhancement effect on the glass transition temperature of epoxy insulating materials. Among them, the glass transition temperatures of bisphenol F and bisphenol AF epoxy insulating materials increased by 6.7% and 7.7%, respectively. The increase in the glass transition temperature of epoxy insulating materials has also further expanded the service scenario range of the materials.

[0081] Figure 7It is the mass change curve of the epoxy insulation material samples obtained in Examples 1, 3, 5, 6, 7, 8 and Comparative Examples 1-3 during the degradation process. In terms of the chemical degradation of epoxy insulation materials, by comparing the degradation rates of unmodified and Schiff base extended modified epoxy insulation material samples in 0.1M hydrochloric acid / methanol solution (hydrochloric acid: methanol = 1:9), it can be found that the chemical degradation rate of the unmodified epoxy cross-linked network (Comparative Examples 1, 2 and 3) in the weakly acidic degradation agent is only 0.008~0.015g / h. This shows that the epoxy insulation material has almost no chemical degradation ability in the degradation agent. When the Schiff base chain segment that responds to pH is constructed in the epoxy cross-linked network, the chemical degradation rate of the epoxy cross-linked network will increase from 0.008~0.015g / h to 0.25~0.31g / h. Its chemical degradation rate has been significantly improved, and an order of magnitude change has occurred. Moreover, as the content of Schiff base segments constructed in the epoxy cross-linked network increases, the depolymerization ability of the epoxy cross-linked network also increases. The chemical degradation rate of epoxy insulation material further increased from 0.27g / h to 0.35g / h. This may be because the Schiff base segments in the epoxy cross-linked network that respond to pH changes replace the original epoxy-anhydride cross-linking sites, which significantly improves the depolymerization ability of the epoxy cross-linked network. In addition, for bisphenol F and bisphenol AF epoxy resins, after the Schiff base segments are constructed in the epoxy cross-linked network, the degradation rate of epoxy insulation materials in 0.1 M hydrochloric acid / methanol mixed solution is also significantly improved. Among them, the chemical degradation rates of bisphenol F and bisphenol AF epoxy insulation materials reached 0.25g / h and 0.29g / h, respectively, which also shows the universal effect of this technical method on improving the chemical degradation ability of epoxy resin systems. Overall, the construction of Schiff base segments in the epoxy cross-linked network has a very significant promoting effect on the degradation performance of insulating materials.

[0082] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.

[0083] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

[0084] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high-strength insulating Schiff base degradable epoxy resin material, characterized in that: The steps include: S1. Weigh a Schiff base building block, an epoxy resin and a phase transfer catalyst in a molar ratio of (0.1-0.3): 1: (0.001-0.003); the molecular structure of the Schiff base building block is: , Among them, the R group is C6H4, C 12 H8O、C 13 H 10 , C 15 H 14 and C 13 One of H8F6; The epoxy resin and the Schiff base building block are mixed, stirred and dissolved at 90-120°C to form a uniform mixed solution, a phase transfer catalyst is added, the heating temperature is adjusted to 130-160°C, stirring is continued at this temperature for 6-12 hours, and cooling is performed after the reaction is completed to obtain the Schiff base chain extension modified epoxy resin; S2. Weigh the Schiff base chain-extending modified epoxy resin, the anhydride curing agent and the amine accelerator in a mass ratio of 100:(60-90):(0.005-0.015); The epoxy resin modified by Schiff base chain extension and the acid anhydride curing agent are placed in a reaction kettle, heated and stirred at 80-120°C to form a uniform mixed liquid, the mixed liquid is subjected to a first degassing treatment, an amine accelerator is added during the treatment, and the degassed mixed liquid is poured into a preheated mold, subjected to a second degassing treatment, cured, cooled to room temperature and then demolded, thereby obtaining an epoxy insulating material with interchain Schiff base segments.

2. The method for preparing the high-strength insulating Schiff base degradable epoxy resin material according to claim 1, characterized in that: The epoxy resin described in step S1 is one or a combination of two or more of glycidyl ether, glycidyl ester, aliphatic and alicyclic epoxy resins.

3. The method for preparing the high-strength insulating Schiff base degradable epoxy resin material according to claim 1, characterized in that: The phase transfer catalyst described in step S1 is one or a combination of two or more of onium salts, open-chain polyethers, tertiary amines, crown ethers, thioethers and quaternary ammonium salts.

4. The method for preparing the high-strength insulating Schiff base degradable epoxy resin material according to claim 1, characterized in that: The anhydride curing agent described in step S2 is one or a combination of two or more of phthalic anhydride, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride and methylnadic anhydride.

5. The method for preparing the high-strength insulating Schiff base degradable epoxy resin material according to claim 1, characterized in that: The amine accelerator described in step S2 is one or a combination of two or more of aliphatic amine, alicyclic amine, aromatic amine, and heterocyclic amine accelerators.

6. The method for preparing the high-strength insulating Schiff base degradable epoxy resin material according to claim 1, 4 or 5, characterized in that: The specific process of the first degassing treatment, the second degassing treatment and the curing in step S2 is as follows: the mixed liquid is degassed at a vacuum degree of 0.08-0.1 MPa for 10-120 min, an amine accelerator is added, and the vacuum degassing is continued for 5-20 min, and the vacuum condition is removed, and the first degassing treatment is completed; The mixed liquid is then poured into a mold preheated to 80-120°C, placed under heating conditions at 120-140°C for 5-30 minutes to complete the second degassing treatment, and then pre-cured at 120-140°C for 3-9 hours, and then post-cured at 150-170°C for 3-18 hours.

7. The method for preparing the high-strength insulating Schiff base degradable epoxy resin material according to claim 1, 2 or 3, characterized in that: The preparation method of the Schiff base building block in step S1 is as follows: S11, weighing kojic acid, a diamine compound and p-toluenesulfonic acid in a molar ratio of 2: (0.8-1.2): (0.02-0.1); S12. Dissolve kojic acid and diamine compounds in benzene according to the above-mentioned molar ratio, and stir them magnetically at 40-80°C until they are completely dissolved. Then add p-toluenesulfonic acid as a catalyst, adjust the heating temperature to 60-140°C, condense and reflux for 12-24 hours, and after the reaction is completed, filter and evaporate excess benzene to obtain a Schiff base building block product.

8. The method for preparing the high-strength insulating Schiff base degradable epoxy resin material according to claim 7, characterized in that: The diamine compound in step S11 and step S12 is one or a combination of two or more of 4,4'-diaminophenyl ether, p-phenylenediamine, 4,4'-methylenedianiline, 4,4'-(2,2-propylenediyl)diphenylamine and 4,4'-(perfluoropropane-2,2-diyl)diphenylamine.

9. The method for preparing the high-strength insulating Schiff base degradable epoxy resin material according to claim 7, characterized in that: In step S1 and step S12, the progress of the chain extension modification reaction is tracked by thin layer chromatography.

10. A high-strength insulating Schiff base degradable epoxy resin material obtained by the method for preparing a high-strength insulating Schiff base degradable epoxy resin material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Application of thiobenzimidazolone Schiff base in inhibition of tyrosinase activity

    CN111840282A

  • Pyrone compound as well as preparation method and application thereof

    CN113620935A

  • Recyclable epoxy wind power blade material containing Schiff base structure and recycling method thereof

    CN116333265A

  • Process of modifying epoxy resin with schiff base type liquid crystal epoxy resin

    CN1974657A

  • N-aryl-n'-alicyclic-para-phenylene diamines

    GB835643A

Cited By

  • Functional amine curing agent and vacuum infusion epoxy resin composite preparation and low temperature recovery method

    CN120208842B